Paenibacillus alkalitolerans sp. nov., a bacterium isolated from a salt lake of Turpan City in Xinjiang Province, north-west China - Li, Rui; Zhang, Zhou-Tian-Le; Wang, Yun; Jiang, Gang-Qiang; Yin, Min; Li, Yu; Zhu, Wen-Yong; Tang, Shu-Kun (Folia microbiologica, 2023)
A Gram stain-positive, rod-shaped, motile, aerobic and terminal endospore formation bacterium, designated YIM B00362T, was isolated from saline soil samples collected from a salt lake in Xinjiang Province, north-west China. Phylogenetic analysis based on the 16S rRNA gene sequences and whole genomes indicated that the isolate belongs to the genus Paenibacillus. However, the highest sequence similarity between strain YIM B00362T and the relatives was only 94.4%. Moreover, the DNA-DNA relatedness and ANI values between the novel isolate and the relative type strain, Paenibacillus antri SYSU K30003T was 13.6% and 70.3%, respectively. The major cellular fatty acids were anteiso-C15:0, C16:0 and the major quinone was MK-7. The isolate contained meso-diaminopimelic acid as the diagnostic diamino acid and the major polar lipids were diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine, phosphatidylglyceride, and two unidentified polar lipids. The genomic DNA G + C content was 50.9 mol%. The major whole-cell sugars contained glucose and galactose. On the basis of physiological, phenotypic, and chemotaxonomic data, strain YIM B00362T represents a novel species of genus Paenibacillus, for which the name Paenibacillus alkalitolerans sp. nov. is proposed. The type strain is YIM B00362T (= KCTC 43272 T = CGMCC 1.18801 T = NBRC 114667 T).
Keywords: Sequence Analysis, DNA; RNA, Ribosomal, 16S; Phylogeny; DNA, Bacterial; Paenibacillus; mastné kyseliny; fosfolipidy; Lakes; China; sekvenční analýza DNA; fylogeneze; Phospholipids; RNA ribozomální 16S; Fatty Acids; jezera; DNA bakterií; Čína